2021
DOI: 10.1177/00332941211051263
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Wave Study On The Associations Of Burnout With Depression And Anxiety: The Mediating And Moderating Role Of Perceived Family Support

Abstract: Studies have shown strong associations between burnout and depression and burnout and anxiety but their exact interrelationships still remain unclear. Few studies have examined the psychosocial mechanisms that might underlie these two relationships. Non-work social factors such as perceived family support can affect mental health. The present study investigated the distinctiveness and the reciprocal associations between burnout and depression, and burnout and anxiety by collecting data twice over an 8 month in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The role of support in shaping burnout may therefore be more complex than simply acting as a buffer against stress. As noted by Koutsimani and Montgomery, 41 social relationships can act as a stressor for people experiencing considerable levels of distress. It is possible that people who are highly distressed or burnt‐out experience diminishing returns from social investments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of support in shaping burnout may therefore be more complex than simply acting as a buffer against stress. As noted by Koutsimani and Montgomery, 41 social relationships can act as a stressor for people experiencing considerable levels of distress. It is possible that people who are highly distressed or burnt‐out experience diminishing returns from social investments.…”
Section: Discussionmentioning
confidence: 99%
“…These data highlight the importance of considering the specific mechanisms by which social support might prevent burnout. For example, Koutsimani and Montgomery 41 reported that perceived family support mediated the relationships between depression and exhaustion (a subdimension of burnout), but not between burnout and depression or burnout and anxiety. The role of support in shaping burnout may therefore be more complex than simply acting as a buffer against stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study includes the perceived family support variable into the model because of the consideration that working women spent more time with their families due to the work-from-home policy during the Covid-19 pandemic. Many previous studies have proven the effect of perceived family support on anxiety levels (Largani et al, 2022;Jafari & Shahriari, 2021;Koutsimani & Montgomery, 2021). However, COR Theory warns of potential social costs (Hobfoll, 2001b).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Burnout represents a major public health concern (Shi et al., 2019), has recently been added to the international classification of diseases (ICD‐11) by the World Health Organisation (WHO) (2019) and is recognised in some European countries as a work‐related disorder and occupation disease (Koutsimani & Montgomery, 2021). Symptoms of burnout can include withdrawal, fatigue, low work morale, decreased job satisfaction (Shi et al., 2019) and has been shown to predict psychological and physical consequences, including type 2 diabetes, musculoskeletal disorder (Armon et al., 2010), cardiovascular disease (Toker et al., 2012), insomnia and depressive symptoms (Armon et al., 2008).…”
Section: Introductionmentioning
confidence: 99%